Solidarity-Based Content Sharing on Social Media: A Closer Look at the Language Style among Millennial Social Platform Users - Saragih, Mandra; Aisyaroh, Yola Ayudi (International Journal of Multidisciplinary Approach Research and Science, 2023)
Social Media platforms have shaped diverse linguistic issues through informal language use, language adaptation and change, linguistic creativity and global communication. The current study reveals the issues about investigating about language style and linguistic form of solidarity expression used by the millennial community on social media platforms. Thirty respondents who aged about 23-43 years old considered as millennial participated in this study and inquired through open-ended questionnaire.  The data was probed by using grounded theory proposed by Creswell. The findings exposed that language style were realized for certain communication purposes and based-social context oriented, solidarity expression was shown through a different linguistic form to reveal ideas, feeling, empathy, caring, respect, moral justice and kinds of arguments. after deeply investigated, there were four types of language styles that are dominantly used by millennial on this social media platform, namely formal language style, informal language style, slang language style and colloquial language style, unfortunately, many people abuse social media as a platform for venting their anger and their disappointment by using disrespectful language and behaviors are frequently observed online. Consequently, this scholarly paper also provides advice on the user of social media platform must possess a range of skills including linguistic knowledge, sociocultural knowledge, and the ability to use language in appropriate ways depending on the specific communicative context.